Challenging Englishness: Rebranding and rewriting national identity in contemporary English fiction - Böhme, Anna Katharina; Justus Liebig University Giessen (My University, 2012)
The perception of English national identity underwent notable changes towards the end of the 20th century. Since the mid-1990s, a changing zeitgeist and the political and cultural developments in England and Britain have led to a redefinition of national self-images. The turn of the millennium can be seen to mark the heyday of a "rebranded" version of Englishness. Literature negotiates different versions and aspects of national identity. Contemporary novels take up existing cultural plots and schemata and creatively rewrite them. The three selected novels exemplify different ways in which contemporary literature challenges Englishness: How to be Good (Nick Hornby, 2001) questions middle-class identity, White Teeth (Zadie Smith, 2000) sheds light on Englishness in postcolonial London and England, England (Julian Barnes, 1998) self-reflexively examines contemporary rebranding processes. These three texts are considered in relation to fourteen additional novels from around 1990 to 2010. In line with the New Historicist approach, the novels are seen as parts of their contemporary cultural contexts, rather than as isolated entities. At the same time, this approach allows for a close reading of the novels according to narratological categories. It permits us to understand the narratives as part of the discourse on Englishness that influences later discourses. Literature can thus contribute to the redefinition and rebranding of Englishness by offering various versions of identity construction.The narrative strategies employed in the novels that contribute to the rewriting and challenging of Englishness can be organised into three main areas: first, the employment of generic, stylistic and formal features; second, techniques of narrative transmission and focalisation, and third, semantisation of space. Through these narrative techniques, the novels negotiate a number of cultural concepts and aspects including cultural memory, history, invented traditions and self-images. In particular, they question the making of history and historiography and their role in constructing collective memory and national identity. Several of the discussed narratives deal self-reflexively with cultural concepts, factors and processes of identity construction, thereby giving rise to meta-comments in a fictional environment.By renegotiating existing English narratives, icons and topoi, the novels can support and perpetuate these premediated schemata or dismantle them as obsolete for today s society. Moreover, they have the potential to create new schemata from a contemporary perspective, thereby contributing to processes of canonisation, iconisation and topicalisation in the discourse of rebranding Englishness.Contemporary novels focus on class and ethnicity as the key identity markers that are used to challenge Englishness. While the class system remains a rather stable factor, ethnicity is represented as an increasingly hybrid concept. The novels also take up political discussions about national identity of the time and critically revise their potential for society. To these ends, literature has functioned as a powerful means of influencing the discourse of rebranding Englishness at the time around the millennium by constantly challenging perceptions of national identity.
Keywords: Englishness; nationale Identität; Remediation; zeitgenössischer Roman; Englishness; national identity; remediation; rewriting; contemporary novels; ddc:820